Simultaneous Occurrence of Duane Retraction Syndrome with Marfan Syndrome - Mihir Kothari; Florence Manurung; Bhavesh Mithiya (Case Reports in Ophthalmological Medicine)
Marfan syndrome (MFS) is an autosomal dominant disorder of connective tissue, while Duane retraction syndrome (DRS) is a congenital cranial dysinnervation disorder (CCDD) which can be transmitted as autosomal dominant disorder in 5–10% of patients. In this paper, we present an 8-year-old girl who presented with left eye DRS and bilateral subluxation of the lens associated with MFS in absence of familial involvement. To our knowledge this is the first case report of DRS with MFS. The occurrence of these syndromes together is very rare and appears to be coincidental.